2008
DOI: 10.1097/qai.0b013e31815e4041
|View full text |Cite
|
Sign up to set email alerts
|

Limited Knowledge and Use of HIV Post- and Pre-Exposure Prophylaxis Among Gay and Bisexual Men

Abstract: PEP awareness and use were modest and PrEP use was rare among gay/bisexual men in California. Although PrEP is not currently recommended, community education on the availability of PEP is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
7
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(96 citation statements)
references
References 19 publications
8
80
7
1
Order By: Relevance
“…In accordance with these reports, an up-regulation of the expression of human ·-defensins and S100 A8 and A9 in tear fluids of pterygium patients provides additional indications for a connection between pterygium and chronic ocular surface inflammation (38). Another study has reported the up-regulation of phospholipase D (PLD) types 2, 3 and 4 in pterygium, compared with normal conjunctiva (39). PLD are involved in various processes, including inflammation, cell differentiation, apoptosis and wound healing and the detection of PLD alterations in pterygium supports their potential role in pterygium pathogenesis (39).…”
Section: Concepts Of Inheritancesupporting
confidence: 59%
See 1 more Smart Citation
“…In accordance with these reports, an up-regulation of the expression of human ·-defensins and S100 A8 and A9 in tear fluids of pterygium patients provides additional indications for a connection between pterygium and chronic ocular surface inflammation (38). Another study has reported the up-regulation of phospholipase D (PLD) types 2, 3 and 4 in pterygium, compared with normal conjunctiva (39). PLD are involved in various processes, including inflammation, cell differentiation, apoptosis and wound healing and the detection of PLD alterations in pterygium supports their potential role in pterygium pathogenesis (39).…”
Section: Concepts Of Inheritancesupporting
confidence: 59%
“…Another study has reported the up-regulation of phospholipase D (PLD) types 2, 3 and 4 in pterygium, compared with normal conjunctiva (39). PLD are involved in various processes, including inflammation, cell differentiation, apoptosis and wound healing and the detection of PLD alterations in pterygium supports their potential role in pterygium pathogenesis (39).…”
Section: Concepts Of Inheritancementioning
confidence: 99%
“…Hyperosmotic stress has been reported to induce cultured HCE-T cell death through various signaling pathways, mediated in part by activation of c-jun N-terminal kinase (JNK), extracellular signal-regulated kinase (ERK), and mitogenactivated protein kinase (MAPK) signaling pathways (Piacentini et al, 2002;Luo et al, 2004;Tong et al, 2008). However, these studies did not look at the relevance of TGM-2 in the JNK, ERK, or MAPK signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Further inflammatory cascades 31 Phospholipase D Further inflammation and cellular differentiation 121 Cystatin C Regulation of extracellular matrix modulators 122 increase in the expression levels of stem cell factor, 131 platelet-derived growth factor (PDGF), 120 connective tissue growth factor (CTGF), 132 and transforming growth factor-beta (TGF-b) 120 have been documented in pterygium. Inflammatory processes of pterygium can trigger reactive wound formation, which may induce dysregulated and inappropriate tissue remodeling, fibroproliferation, enhanced vascularization, and deposition of the extracellular matrix, leading to the formation of hypertrophic scarring.…”
Section: Cox2mentioning
confidence: 99%
“…31 An increase in phospholipase D, an enzyme involved in inflammation and cellular differentiation, was also found in pterygium. 121 Cystatin C, an inhibitor of cysteine proteinases, is overexpressed in pterygium and is more abundant in tears from patients with the disease. This protein could serve as a natural mechanism of protection against inflammation.…”
Section: Inflammatory Mediators and Growth Factorsmentioning
confidence: 99%